Anglik, Niemiec i ich języki w międzywojennych numerach czasopisma „Neofilolog” - Kotlarska, Irmina; Przyklenk, Joanna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The article presents the images of an Englishman and a German as created in the interwar editions of the quarterly “Neofilolog”. The research was based on an analysis of selected excerpts from Polish-language press texts in which the terms Anglik (‘Englishman’), Niemiec (‘German’), Anglia (‘England’), Niemcy (‘Germany’), angielski (‘English’ adj.) and niemiecki (‘German’ adj.) were identified. The inclination to articulate opinions about individuals who exhibited a distinct ethnolect was a prominent feature of glotto-type discourse during the interwar period. This phenomenon can be attributed to the prevailing belief in the educational merits of foreign language instruction. The collected examples were subjected to linguistic analysis in accordance with the findings of the linguistic world image theory. This allowed us to ascertain that the images of native English and German speakers were shaped primarily by the context of Poland’s political and economic interests and the regained independence. The desire to build a reborn state community shaped the portrayal of individuals from both nations as exemplars of elevated culture, worthy of emulation within the Polish context. The personality traits attributed to the two representatives are distinct, as is the attitude towards them which is formed by the disparate levels of direct contact with both nations throughout history.